2011
DOI: 10.1590/s1517-86922011000300010
|View full text |Cite
|
Sign up to set email alerts
|

Perfil da aptidão física dos praticantes de Le Parkour

Abstract: The aim of this study was to evaluate physical fitness of Le Parkour practitioners in the city of Curitiba-PR. 13 male subjects (19.46 ± 2.82 years) who have been practicing the activity for more than six months participated in the study. Anthropometry and tests of physical fitness (back-and-forth 20-meter running, 1-minute abdominal, flexion and extension of the arms, vertical and horizontal push, sit-and-reach test and Wingate) were performed. The results were analyzed using descriptive statistics (mean and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
1
8
0
4
Order By: Relevance
“…Our findings demonstrated a significant increase in explosive power after parkour training as standing broad jump increased by 7.4 % over the 10-week intervention. Our post test findings are very similar to those reported in the crosssectional study of Leite et al [22] who reported average standing broad jump of 253 ± 23 cm. We can classify our average posttest value into the category higher than the average.…”
Section: Effect Of Parkour On Strengthsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings demonstrated a significant increase in explosive power after parkour training as standing broad jump increased by 7.4 % over the 10-week intervention. Our post test findings are very similar to those reported in the crosssectional study of Leite et al [22] who reported average standing broad jump of 253 ± 23 cm. We can classify our average posttest value into the category higher than the average.…”
Section: Effect Of Parkour On Strengthsupporting
confidence: 91%
“…While no study has investigated the specific effects of a parkour training intevention, a cross-sectional study by Leite et al [22] reported that the average O 2 peak in a small group of parkour practioners (mean age = 19.5 ± 2.8 yr) who had been performing parkour for at least 6 months, was 44.2 ± 5.6 ml·min -1 ·kg -1 . The difference between our pretest values and Leites´ study could be caused by the use of a field test for estimating O 2 peak in Leites´ study, which may have underestimated the true O 2 peak.…”
Section: Effect Of Parkour On Cardiorespiratory Fitnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Embora, uma característica muito forte da prática é sua realização na maioria das vezes de forma empírica, acíclica e em ambientes variados, raramente com acompanhamento profissional 3 .…”
Section: Introductionunclassified
“…Para Leite et al 3 o parkour pode ser praticado por qualquer pessoa, desde que respeite sua condição física e suas limitações, para os pesquisadores a prática não possui grandes exigências físicas. Porém até o momento nenhum estudo foi encontrando na literatura, que se propôs em investigar as exigências do metabolismo energético e do sistema cardiorrespiratório dos praticantes durante uma sessão de parkour, a fim de determinar a intensidade de esforço.…”
Section: Introductionunclassified